A study into the perceptions of educators on the new competence based curriculum’s formative and summative assessment in four secondary schools in Muzarabani district of Mashonaland Central in Zimbabwe - Chisenga, George (Midlands State University, 2019)
The reason for carrying out this study was to investigate the perception of educators on the new competence based curriculum‟s two assessment procedures of formative and summative in four secondary school of Muzarabani District of Mashonaland Central Province.